Design and Development of a Chatbot-Integrated Website Profile for Madrasah Tsanawiyah to Improve Academic Information Services - Amelia Nurhayati; Sulidar Fitri; Hani Rubiani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid advancement of information technology has driven educational institutions to improve the quality of their information services. MTs Sambong Jaya faces challenges in delivering academic information due to its inactive website, resulting in limited accessibility for students and the community. This study aims to develop a madrasah profile website integrated with a rule-based chatbot to enhance the effectiveness of academic information services. This research employed the Research and Development (R&D) method based on the Borg and Gall model, including needs analysis, planning, development, validation, testing, and evaluation stages. The chatbot was designed using predefined question–answer patterns to provide automated responses to user inquiries. The evaluation results show that expert validation achieved a score of 90% (Very Feasible), Blackbox Testing indicated a 100% success rate for all system functions, and user responses reached 81.71% (Very Good). These findings indicate that the developed system is functional, user-friendly, and capable of improving access to academic information.